Experimental Study on the Effect of Chemical Composite Additives on Heat Release Characteristics of Coal Oxidation Spontaneous Combustion. Issue 4 (12th March 2021) - Pan, Rongkun; Ma, Junwei; Wu, Shuaidong; Tang, Wentao; Yu, Minggao; Jia, Hailin
ABSTRACT: To study the effect of chemical composite additives (CCAs) on the heat release characteristics of coal oxidation spontaneous combustion, this paper develops a CCA comprising multiple chemical reagents that is formulated into different concentrations and used to treat coal samples. Microcalorimetry technology with high precision and high sensitivity was used in this experimental research. The heat release parameters of the oxidation of different treated coal samples were obtained and compared by varying the heating rate. The experimental results show that the general trend for coal is first absorbing heat and then releasing heat with increasing temperature, and there is a "step-like" trend in the heat releasing stage. For the same heating rate, water treatment and CCA treatment delay the temperature increase in the coal in the heat absorbing stage, and in the heat releasing stage, water treatment increases the heat release rate and maximum heat flow. CCA treatment decreases the heat release parameters value of the oxidation of coal, and the effect is increased with the increasing CCA concentration. The thermal analysis kinetics method was used to study the coal oxidation reaction. CCA treatment can increase the activation energy of coal, increase the difficulty of reaction process and reduce the heat release rate, which has an inhibitory effect on the spontaneous combustion of coal. Increasing the heating rate can accelerate the reaction rate of the system, resulting in an increase in the spontaneous combustion tendency of coal.